Analisis Setelah Akuisisi Saham Perusahaan di Indonesia: Studi Kasus Pada Blibli Dan Ranc (International Forum of Researchers and Lecturers, 2024)
This article examines the business combination carried out by companies in Indonesia, namely the acquisition of shares by Blibli. An analysis was carried out on the positive impacts and challenges that had to be faced after Blibli acquired PT Supra Boga Lestari Tbk (RANC). The acquisition of shares affects both companies and digital businesses in Indonesia. The literature review method is used by analyzing previous journals descriptively. The analysis carried out shows that there are positive impacts and challenges that must be faced due to the acquisition of RANC shares. Blibli and RANC are trying to create synergies that can accelerate the omnichannel solutions of both companies, supported by digital technology capabilities.